2017
DOI: 10.1002/mabi.201700255
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Study of In Situ Loaded Antibody and PEG‐Fab NIPAAM Gels

Abstract: Hydrogels can potentially prolong the release of a therapeutic protein, especially to treat blinding conditions. One challenge is to ensure that the protein and hydrogel are intimately mixed by better protein entanglement within the hydrogel. N-isopropylacrylamide (NIPAAM) gels are optimized with poly(ethylene glycol) diacrylate (PEDGA) crosslinker in the presence of either bevacizumab or PEG conjugated ranibizumab (PEG -Fab ). The release profiles of the hydrogels are evaluated using an outflow model of the e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
24
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 18 publications
(26 citation statements)
references
References 86 publications
2
24
0
Order By: Relevance
“…In a previous study conducted in our laboratory, LCST values ranged from 34.3 ± 0.2 to 36.2 ± 0.2°C (p<0.05) for PEGDA amounts from 2-6% (with pNIPAAM-PEGDA hydrogels). 32 Isopropyl groups predominate above the LCST leading to an aggregation mechanism that results in the overall domination of hydrophobicity. 46 The polymer chain retracts from the surrounding solvent in a repulsive force manner.…”
Section: Figures 1 and 2 Lower Critical Solution Temperature (Lcst)mentioning
confidence: 99%
See 1 more Smart Citation
“…In a previous study conducted in our laboratory, LCST values ranged from 34.3 ± 0.2 to 36.2 ± 0.2°C (p<0.05) for PEGDA amounts from 2-6% (with pNIPAAM-PEGDA hydrogels). 32 Isopropyl groups predominate above the LCST leading to an aggregation mechanism that results in the overall domination of hydrophobicity. 46 The polymer chain retracts from the surrounding solvent in a repulsive force manner.…”
Section: Figures 1 and 2 Lower Critical Solution Temperature (Lcst)mentioning
confidence: 99%
“…The use of a collapsible thermoresponsive hydrogel provides the potential for further prolongation of antibody release from an injected hydrogel formulation. Poly(Nisopropylacrylamide) (pNIPAAM) is a thermoresponsive polymer [26][27][28][29][30][31][32][33] that is biocompatible, but it is not biodegradable. 34 Incorporation of a HA biodegradable component 35,36 as an IPN in the pNIPAAM network is one strategy to allow the clearance of pNIPAAM.…”
Section: Introductionmentioning
confidence: 99%
“…They are also useful for circumventing the need for frequent repeat injections—which presents several risks and complications to patients—by acting as a drug depot even for unstable protein molecules [ 140 ]. There are a number of in-situ gelling systems reported for ocular delivery of proteins [ 225 , 300 , 301 , 302 , 303 , 304 , 305 , 306 , 307 , 308 ]. Xue et al [ 305 ] developed thermosensitive gels of anti-VEGF drugs (bevacizumab and aflibercept) using a PEG-polypropylene glycol (PPG)-PCL multiblock copolymer (hydrophilic–hydrophobic biodegradable copolymer) [ 305 ].…”
Section: Polypeptide Deliverymentioning
confidence: 99%
“…To design an efficient in-situ gelling system, it is vital that the rate of reaction be rapid enough to encapsulate the protein and prevent the removal of gelling precursors, but sufficiently slow to allow the injection of the pre-gel solution [ 271 ]. Awwad and co-workers [ 225 , 300 , 308 ] have reported the in vitro delivery of antibodies with thermoresponsive hydrogels. These authors [ 308 ] reported the sustained release (over 30 days) of bevacizumab and PEG-conjugated ranibizumab (PEG-Fab rani ) from a crosslinked N -isopropylacrylamide (NIPAAM) hydrogel [ 308 ].…”
Section: Polypeptide Deliverymentioning
confidence: 99%
See 1 more Smart Citation